Βιβλιοκρισία:JEAN-MARIE MARTIN, Byzance et l’Italie méridionale [Bilans de recherche 9], Paris 2014, σελ. ΧΧ + 628. ISBN 978-2-916716-41-1 - ΒΛΥΣΙΔΟΥ Βασιλική (Byzantina Symmeikta, 2016)
Βιβλιοκρισία: Jean-Marie Martin, Byzance et l’Italie méridionale [Bilans de recherche 9], Paris 2014, σελ. ΧΧ + 628. ISBN 978-2-916716-41-1